1960
DOI: 10.1001/jama.1960.73020330015014a
|View full text |Cite
|
Sign up to set email alerts
|

Optic and Peripheral Neuritis

Abstract: Chloramphenicol is one of the most valuable antibiotics available to the physician,1 although in rare instances it may cause severe hematopoietic reactions.2 It is the purpose of this paper to emphasize another apparent severe toxic reaction\p=m-\theoccurrence of optic and peripheral neuritis. Report of a CaseThe patient was a 20-year-old man who had been in good health until Oct. 21, 1957, when he was treated with penicillin for a "flu-like" syndrome. Three days later genitourinary symptoms occurred; he becam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1961
1961
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(3 citation statements)
references
References 10 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…It was reported that before the chronic phase of the disease, the patient had suffered from an acute pneumonic phase. A second case of melioidosis, which was probably acquired in Panama, was reported in 1957 [ 20 , 21 ]. The patient was a 20-year-old male who was treated for ‘flu-like syndrome’.…”
Section: Review Of Melioidosis Cases and Presence Of B mentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that before the chronic phase of the disease, the patient had suffered from an acute pneumonic phase. A second case of melioidosis, which was probably acquired in Panama, was reported in 1957 [ 20 , 21 ]. The patient was a 20-year-old male who was treated for ‘flu-like syndrome’.…”
Section: Review Of Melioidosis Cases and Presence Of B mentioning
confidence: 99%
“…He had pyuria, and a chest roentgenogram showed a small infiltrate in the upper lobe of the left lung. After one month, he developed an acute septic arthritis of the shoulder joint; pus was removed, and Pseudomonas pseudomallei was isolated in culture [ 20 ]. However, in the two aforementioned cases, the cultures were not available for further studies, and could not be considered as verified cases of melioidosis.…”
Section: Review Of Melioidosis Cases and Presence Of B mentioning
confidence: 99%
“…penicillin or a semisynthetic derivate, 1 chloramphenicol, 2 and metronidazole. 3 Nitrofurantoin treatment has caused sensory-motor neuropathy 4 and dapsone treatment has caused motor neuropathy.…”
Section: Introductionmentioning
confidence: 99%